The Role of Spiritual Intelligence Moderation in Improving Organizational Commitment and Employee Performance at Ministry of Religion Regional Office - Poniman Poniman; Evelyn Wijaya; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
In carrying out government and development activities, the position and role of civil servants are crucial. Civil servants are elements of the state apparatus that carry out elements of government and development in an effort to achieve organization goals. This research aims to analyze impact on islamic leadership and organization culture to organizational commitment and employee performance with spiritual intelligence as moderating variable. Research population were all employees at Ministry of Religion Regional Office of Riau Province with total sample as 150 respondents with cencus method. Data analysis used Structural Equation Modeling (SEM) with SMARTPLS 4.0.0. Research result show that organization culture has impact on organizational commitment and employee performance, islamic leadership has impact on employee performance but has not impact on organizational commitment. Organizational commitment has not impact on employee performance. Spiritual intelligence strengthen impact on organization culture to organizational commitment and employee performance. Spiritual intelligence weaken impact on islamic leadership to organizational commitment and employee performance. To maximize individual potential and enhance overall organizational results, spiritual intelligence development should be incorporated into training and culture.